Efficient microorganism and lixiviate vermicompost applications increase the cucumber production - Hurtado, Alexander Calero [UNESP]; Rodríguez, Elieni Quintero; Díaz, Yanery Pérez; Hurtado, Yainier González-Pardo; Lorenzo, Tomasa Norma González (Universidad de Ciencias Aplicadas Y Ambientales - UDCA, 2019)
The main problems of cucumber production reside fundamentally by the mineral fertilizer s shortage, climatic affectation and limited use of biofertilizers, which is important to looking for efficient alternatives that increase productivity, rationality and sustainability. The objective of this research was to evaluate the effect of individualized and associated use of biofertilizers efficient microorganisms and lixiviate vermicompost on the agro-productive increase of cucumber. The work was developed in the productive unit El Estadio, Sancti Spíritus, Cuba, between January to April 2015 and Su Yi Sung cultivar of cucumber was used. The treatments used were a control (no application), soil inoculation and foliar applications with efficient microorganisms and lixiviate vermicompost at 100 and 200mL L-1, and soil inoculation with efficient microorganisms at 100mL L-1 and foliar applications with lixiviate vermicompost at 100mL L-1. The following variables were observed: number of leaves, female flowers and fruits per plant, length of fruits (cm), mass of fruits (g) and yield (kg m-2). The results showed that the individual and combined application of biofertilizers had a biostimulants effect on cucumber production. The efficient microorganism s application at 100mL L-1 and the combination with lixiviate vermicompost to 100mL L-1 constituting a sustainable alternative in the cucumber productivity, especially because they increased the number of leaves, female flowers, fruits, mass and length of fruits and increasing the yield by 42 % compared to control treatment.
Microorganismos efi cientes y vermicompost lixiviado aumentan la producción de pepino
Keywords: Biofertilizer; Cucumis sativus; Foliar application; Soil inoculation; Yield.